2003
DOI: 10.1038/nrg1110
|View full text |Cite
|
Sign up to set email alerts
|

Condensin and cohesin: more than chromosome compactor and glue

Abstract: Two related protein complexes, cohesin and condensin, are essential for separating identical copies of the genome into daughter cells during cell division. Cohesin glues replicated sister chromatids together until they split at anaphase, whereas condensin reorganizes chromosomes into their highly compact mitotic structure. Unexpectedly, mutations in the subunits of these complexes have been uncovered in genetic screens that target completely different processes. Exciting new evidence is emerging that cohesin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
205
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(214 citation statements)
references
References 106 publications
4
205
0
1
Order By: Relevance
“…For example, condensin has been implicated in the SIR2-mediated silencing at the rDNA and telomeres (Machin et al 2004), and certain condensin mutations can also affect silencing at the mating-type loci (Bhalla et al 2002), which is also SIR2-mediated. While silencing near tRNA genes (and their nucleolar localization) is mechanistically distinct from the other types of silencing and independent of SIR2 (L. , it has been suggested previously that condensin may influence interphase chromosome arrangements in ways that impact gene regulation (Hagstrom and Meyer 2003). Our combined evidence Cold Spring Harbor Laboratory Press on May 10, 2018 -Published by genesdev.cshlp.org Downloaded from that condensin is required for tRNA gene clustering and for tgm silencing suggests that the complex plays a very important role in the nuclear architecture and that this influences nuclear functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, condensin has been implicated in the SIR2-mediated silencing at the rDNA and telomeres (Machin et al 2004), and certain condensin mutations can also affect silencing at the mating-type loci (Bhalla et al 2002), which is also SIR2-mediated. While silencing near tRNA genes (and their nucleolar localization) is mechanistically distinct from the other types of silencing and independent of SIR2 (L. , it has been suggested previously that condensin may influence interphase chromosome arrangements in ways that impact gene regulation (Hagstrom and Meyer 2003). Our combined evidence Cold Spring Harbor Laboratory Press on May 10, 2018 -Published by genesdev.cshlp.org Downloaded from that condensin is required for tRNA gene clustering and for tgm silencing suggests that the complex plays a very important role in the nuclear architecture and that this influences nuclear functions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although it is possible that condensin mutants decluster the tRNA genes through disorganization of nucleolar architecture, direct condensin participation in the clustering seems likely. Prior to this work, only a small number of interphase condensin functions were explored in various organisms (Hagstrom and Meyer 2003), including gene regulation and centromere organization. Of particular interest is the condensin-like dosage compensation complex in Caenorhabditis elegans, which is responsible for the sex-determining X-chromosome repression (Hagstrom and Meyer 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that Nipped-B, a cohesin-loading factor, is required for long-range gene activation initially suggested that cohesin itself might facilitate activation by, for example, stabilizing "pairing" interactions between distant enhancers and promoters in a manner similar to the way it holds sister chromatids together (Dorsett 1999;Hagstrom and Meyer 2003). This hypothesis was negated, however, when it was discovered that reducing the levels of cohesin subunits by RNAi or mutation increased cut expression, which is opposite to the effect of Nipped-B mutations (Rollins et al 2004;Dorsett et al 2005).…”
Section: Effects Of Sister Chromatid Cohesion Factors On Long-range Gmentioning
confidence: 99%
“…Like the Nipped-B family, cohesin also has roles besides sister chromatid cohesion in meiosis, DNA repair, gene expression, and human development (reviewed in Dorsett 2007;Nasmyth and Haering 2005;Hagstrom and Meyer 2003;Hirano 2006;Revenkova and Jessberger 2006). Thus, a central question is whether regulation of cohesin also explains the functions of the Nipped-B family proteins in gene expression and meiosis.…”
Section: Introductionmentioning
confidence: 99%